13th International Conference on Electrostatics - Taylor, D. Martin (Journal of physics. Conference series, 2011)
Electrostatics 2011 was held in the city of Bangor which is located in North West Wales in an area of outstanding natural beauty close to the Snowdonia mountain range and bordering the Irish Sea. The history of the area goes back into the mists of times, but a continuous technological thread can be traced from the stone- and bronze-age craftsmen, who inhabited the area several thousand years ago, via the civil engineering and fortifications of the Romans and Edward I of England, through Marconi's long-wave trans-Atlantic transmitter near Caernarfon to the conference host. The School of Electronic Engineering at Bangor University has contributed much to the discipline of Electrostatics not only in teaching and research but also in supporting industry. It was a great pleasure for me, therefore, to have the pleasure of welcoming the world's experts in Electrostatics to Bangor in April 2011. In my preface to the Proceedings of Electrostatics 1999, I reported that almost 90 papers were presented. Interestingly, a similar number were presented in 2011 testifying to the importance and endurance of the subject. The all-embracing nature of electrostatics is captured in the pictorial depiction used for the conference logo: a hand-held plasma ball with its close link to gaseous discharges and the superimposed Antarctic aurora highlighting the featured conference themes of atmospheric, planetary and environmental electrostatics. Leading these themes were three invited contributions, the first by Giles Harrison who delivered the Bill Bright Memorial Lecture 'Fair weather atmospheric electricity', Carlos Calle on 'The electrostatic environments of Mars and the Moon' and Istvan Berta on 'Lightning protection – challenges, solutions and questionable steps in the 21st century'. Leading other key sessions were invited papers by Atsushi Ohsawa on 'Statistical analysis of fires and explosions attributed to static electricity over the last 50 years in Japanese industry' and Antonio Ramos on 'Electrohydrodynamic pumping in microsystems'. Of the papers submitted for publication 69 passed through the thorough review process and I take this opportunity to warmly thank the reviewers for their constructive criticism and rapid turnaround which has allowed the Proceedings to be delivered to the publisher on time. It is a pleasure also to thank members of the International Advisory Panel, and the Organizing and Programme Committees for their guidance and suggestions and especially Claire Garland and her team at the Institute of Physics for their support, all of which ensured a successful and enjoyable conference. Special thanks are due to Jeremy Smallwood for organising the pre-conference workshop, to Tom Jones, Martin Glor and Dave Swenson for their highly informative and educational contributions at the workshop, to CST for organising the simulation workshop, and to CST and JCI Chilworth for their much appreciated sponsorship of the conference. I am sure you will enjoy reading this record of Electrostatics 2011, covering as it does the wide range of subjects upon which static electricity impinges. Especially important is the development of electrostatic-based methods for reducing atmospheric pollution. In this context it is interesting to see how Masuda's work on the surface-discharge-based Boxer charger, first reported over 30 years ago, has now developed into dielectric barrier discharge (DBD) systems for the removal of noxious molecules from industrial and vehicle exhaust gases. Thanks to our hard working conference chairman, Paul Holdstock, the conference retained its now well-established reputation for providing a friendly, sociable atmosphere for discussing the newest developments in this important scientific area. Finally, my sincere thanks go to all the presenters and to all those who attended and contributed to another successful conference. Professor D. Martin TaylorProceedings EditorBangor, May 2011